Travel and intercultural communication : going north - Björk, Eva Lambertsson; Eschenbach, Jutta (Cambridge Scholars Publishing, 2017)
This volume brings together the proceedings of "Going North: An Interdisciplinary Conference on Travel and Intercultural Communication" held in Halden, Norway, in 2016. Today's world is akin to a global network where spatial, linguistic and cultural mobility reshapes our identities. This mobility is unprecedented in its scope, and is caused by a multitude of reasons, from purely leisurely travel to desperate flight. The "Going North" conference addressed the role of travel - past and present - and intercultural communication connected to travel. The book brings together texts focusing on going